Foundations of Effective Classroom Management - Kelsey M. Thornton; Tre Easterly; Ed Osborne (EDIS, 2021)
Classroom management can be challenging for teachers. While managing a classroom requires flexible approach, there are some basic strategies than can be used to make the classroom safe and engaging. This new 3-page article provides recommendations to teachers to manage student behavior in the agriculture classroom. Written by Kelsey M. Thornton, R. G. (Tre) Easterly III, and Ed Osborne, and published by the UF/IFAS Department of Agricultural Education and Communication. https://edis.ifas.ufl.edu/wc381